The suitability of Mytilus edulis as proxy archive and its response to ocean acidification - Heinemann, Agnes (2011)
Past climate changes can be used as indicators of future scenarios, however past climatic changes can not be directly observed. Therefore, the reconstruction of past abiotic conditions can approximated using chemical or isotopic proxies. These proxies can be measured in natural archives (e.g. bivalve shells and coral skeletons). One aspect of current climate change is the acidification of the oceans, a phenomenon caused by the oceanic uptake of anthropogenic CO2 and a resulting shift in the marine carbonate system. As a result of this, a drop of mean ocean surface pH by ~0.3-0.7 units can be expected until the year 2100. In relation to geological timescales this drop occurs very fast (~0.1-0.2 units per 100 years) and causes species specific reactions which are not fully studied yet. For example, elevated [CO2] disturbs the acid-base status of extracellular body fluids and the degree of disturbances depends on animals metabolic rates. Especially marine calcifying organisms are influenced in their ability to form CaCO3-shells and skeletons by this decline in pH. The blue mussel (Mytilus edulis) is an important calcifier in many marine ecosystems and in aquaculture. In this Thesis I investigated the impact of ocean acidification on the acid-base status and the calcification of M. edulis in experiments conducted under different seawater pCO2 levels (380-4000 µatm). Furthermore, investigations of M. edulis shells as proxy archive have led to contradictory results. Hence, the impact of elevated pCO2, as well as temperature and salinity on the inorganic shell composition have been investigated in this study to test the suitability of M. edulis shells as a proxy archive in general and for pH construction in particular. Physiological experiments can provide knowledge about acclimation reactions of marine organisms to abiotic stressors but not about their adaptation potential, as the relevant timescales cannot be simulated in laboratory studies. Thus, experiments using already pre-adapted animals from challenging ...